1999
DOI: 10.1073/pnas.96.16.8913
|View full text |Cite
|
Sign up to set email alerts
|

An unusual structural motif of antimicrobial peptides containing end-to-end macrocycle and cystine-knot disulfides

Abstract: Four macrocyclic cystine-knot peptides of 29-31 residues, kalata, circulin A and B (CirA and CirB), and cyclopsychotride, have been isolated from coffee plants but have undetermined physiological functions. These macrocycles and 10 of their analogs prepared by chemical synthesis were tested against nine strains of microbes. Kalata and CirA were specific for the Gram-positive Staphylococcus aureus with a minimum inhibition concentration of Ϸ0.2 M. They were relatively ineffective against Gram-negative bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
445
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(464 citation statements)
references
References 30 publications
13
445
2
4
Order By: Relevance
“…Boc-, 38 microwave-enhanced 24 and Fmoc- 14,30,34,35 based solid-phase peptide synthesis (SPPS) have all been used for cyclotide backbone construction, whilst recent work has shown that bacterial expression can also be an effective approach for 20 smaller scale production of the cyclotide backbone. 25,28 Backbone cyclisation may then be achieved by exposing a suitably side chain protected backbone peptide bearing an amino N-terminus and a carboxy C-terminus to standard peptide coupling conditions, but this approach suffers from 25 multiple drawbacks including poor peptide solubility and the need for high dilution.…”
Section: Chemical Synthesis Of Engineered Mcoti Cyclotidesmentioning
confidence: 99%
“…Boc-, 38 microwave-enhanced 24 and Fmoc- 14,30,34,35 based solid-phase peptide synthesis (SPPS) have all been used for cyclotide backbone construction, whilst recent work has shown that bacterial expression can also be an effective approach for 20 smaller scale production of the cyclotide backbone. 25,28 Backbone cyclisation may then be achieved by exposing a suitably side chain protected backbone peptide bearing an amino N-terminus and a carboxy C-terminus to standard peptide coupling conditions, but this approach suffers from 25 multiple drawbacks including poor peptide solubility and the need for high dilution.…”
Section: Chemical Synthesis Of Engineered Mcoti Cyclotidesmentioning
confidence: 99%
“…Cyclotides are structurally related to plant defensins, which occur ubiquitously throughout the plant kingdom (Craik et al, 1999, and refs. therein;Trabi and Craik;, and antimicrobial activity against several fungal species has been shown (Tam et al, 1999;Jennings et al, 2001). Thus, it will be interesting to determine whether this also accounts for the putative maize cyclotide.…”
Section: Umi Genes Related To Secondary Metabolism and Defensementioning
confidence: 99%
“…A single plant may have at least 12 cyclotide genes and produce dozens of different cyclotides (12)(13)(14). Although an earlier study reported antimicrobial activity (15), it appears that their predominant activity in plants is insecticidal (13,16). Jennings et al (13) demonstrated that Helicoverpa punctigera failed to develop past the second instar stage when raised on artificial diets containing the cyclotide kalata B1 (13).…”
mentioning
confidence: 99%